Condition Monitoring Scheduled Oil Sample on Crane Machine Using the Fuzzy Logic Methode - Syaiful Rizal; Kartika Sekarsari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Maintenance of crane engines in the mining world is very much needed to maintain the engine in good condition and function when used. In crane engine maintenance management, a scheduled oil sample is a form of predictive engine maintenance by taking regular oil samples from the engine to analyze its content and quality in the laboratory. The Fuzzy Logic method used in this study aims to monitor the results obtained from the laboratory so that it can be recognized that the condition of the engine is still in excellent condition (eval A), the state of the engine is still good, and no action has been recommended (eval B), it is recommended action on the engine (eval C) and recommends stopping the engine (eval X)